2016
DOI: 10.1016/j.jad.2016.03.031
|View full text |Cite
|
Sign up to set email alerts
|

Association of CRTC1 polymorphisms with obesity markers in subjects from the general population with lifetime depression

Abstract: Philippe Conus and Chin B. Eap, Association of CRTC1 polymorphisms with obesity markers in subjects from the general population with lifetime depression, Journal of Affective Disorders, http://dx.doi.org/10. 1016/j.jad.2016.03.031 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting galley proof before it is pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 44 publications
1
19
0
Order By: Relevance
“…Recent evidence collected in Crtc1 −/− mice has established that not only the lack of CRTC1 induces hyperphagic obesity 6 , 7 , but it also triggers a depressive-like phenotype, which suggests that CRTC1 plays a role in mood disorder etiology and antidepressant response 8 10 . In agreement with these animal studies, two human investigations have highlighted an association of CRTC1 polymorphisms with body mass index and fat mass, and have suggested that CRTC1 is involved in the high prevalence of overweight and obesity observed in psychiatric patients and in subjects from the general population with major depressive disorder 22 , 23 . Altogether, these findings suggest that CRTC1 is a transcriptional coactivator reciprocally involved in the bidirectional relation between obesity and depression.…”
Section: Introductionmentioning
confidence: 55%
“…Recent evidence collected in Crtc1 −/− mice has established that not only the lack of CRTC1 induces hyperphagic obesity 6 , 7 , but it also triggers a depressive-like phenotype, which suggests that CRTC1 plays a role in mood disorder etiology and antidepressant response 8 10 . In agreement with these animal studies, two human investigations have highlighted an association of CRTC1 polymorphisms with body mass index and fat mass, and have suggested that CRTC1 is involved in the high prevalence of overweight and obesity observed in psychiatric patients and in subjects from the general population with major depressive disorder 22 , 23 . Altogether, these findings suggest that CRTC1 is a transcriptional coactivator reciprocally involved in the bidirectional relation between obesity and depression.…”
Section: Introductionmentioning
confidence: 55%
“…In addition, a human study suggested that CRTC1 polymorphisms are associated with obesity markers in individuals with major depression but not in non‐depressive individuals (Quteineh et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…Indeed, epidemiological evidence supports the association of depression and obesity in both Western and non-Western countries, with a robust bidirectional relationship, independently of antidepressant medications [5,70]. In fact, weight gain related to psychotropic medications appears more to be linked to polygenic risk more than comorbid depression/obesity mechanisms [71]. Despite these limitations, other reports have demonstrated similar spatial correlations in linked pathologies (e.g.…”
Section: Discussionmentioning
confidence: 99%